Akumulacja wewnętrzna kapitału na tle teorii finansowania przedsiębiorstw - Iwin-Garzyńska, Jolanta (Internal Accumulation of Capital in the Theory of Corporate Finance, 2006)
Economic processes that run in every enterprise are determined by capital of the firm. In the literature of the subject the issue of financing sources and financial hierarchy is broadly described. In the theory of corporate finance one can find evidence for superiority of internal over external finance and reverse. The aim of the paper is to find the answer to questions that arise from the discrepancy of conclusions that come from analysis of different financial theories.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 275-285